International conference on sanctions against South Africa ([United Nations], 1981)
Map of Africa with South Africa and Namibia's limits highlighted, and circled; red arrows diverting from circle. Yellow background Poster advertising conference on sanctions against South Africa, held in Paris, 20-27 May, 1981 PO-0237